A long-term quality-of-care score for predicting the occurrence of macrovascular diseases in patients with type 2 diabetes mellitus. (May 2018) - Li, Pi-I; Wang, Jian-Nan; Guo, How-Ran
Highlights: The quality of care score may affect the development of complications of diabetes. Macrovascular diseases are common in patients with Type 2 diabetes mellitus. A scoring system has been proposed in the U.S. to monitor the quality of care. We made modifications and found a better correlation with macrovascular diseases. Scores ≥5 were associated with 64% less macrovascular diseases compared to scores ≤1. Abstract: Aims: The aim of this study was to develop a long-term quality-of-care score to predict the occurrence of macrovascular diseases in patients with type 2 diabetes mellitus, on the basis of the hypothesis that good quality of care can reduce the risk of macrovascular complications. Methods: Using Taiwan's Longitudinal Cohort of Diabetes Patients Database and the medical records in a medical center, we identified the incident patients diagnosed with type 2 diabetes during 1999–2003 and followed them until 2011. A summary score (from 0 to 8) was calculated according to process indicators (frequencies of HbA1c and lipid profile testing and urine, foot and retinal examinations), intermediate outcome indicators (low-density lipoprotein, blood pressure and HbA1c ), and the co-morbidity of hypertension. We used Cox regression models to evaluate the association between the score and the incidence of macrovascular complications. Results: Of the 4275 patients enrolled, 1928 developed macrovascular complication events after a mean follow-up period of 8.2 years. Compared to the risk of developing a macrovascular disease event in patients with scores ≤1, the risk was 64% lower in those with quality-of-care scores ≥5 (adjusted hazard ratio = 0.36; 95% confidence interval: 0.28–0.45). Conclusions: Good quality of care can reduce the risk of macrovascular diseases in patients with type 2 diabetes. The score developed in this study had a significant association with the risk of macrovascular complications and thus can be applied to guiding the care for these patients.